How likely is environmental or patient cross-contamination of Chlamydia trachomatis DNA to lead to false positive results in patients attending our clinic?. Issue 2 (4th October 2012) - Chan, Sum Yee; Jose, Sophie; King, Rebecca; Pakianathan, Mark R; Sabin, Caroline; Sadiq, S Tariq; Hay, Phillip E; Planche, Tim
Abstract : Objectives: Environmental contamination with DNA from Chlamydia trachomatis (CT) has previously been found in Genitourinary Medicine (GUM) clinics. There are no known cases of cross-contamination of clinical samples and no known nosocomial infections. We investigated whether diagnostic samples could become contaminated from the environment by running dummy sample and carrying out a patient-throughput analysis. A total of 29 748 patients attended clinics over a year. Of these, 2860 (9.6%) had a positive Chlamydia test result. Method: (1) A run of dummy samples (60 urine samples and 10 swabs) were processed as normal clinic specimens. (2) Patient-throughput analysis: Patient numbers attending the GUM clinic on a given day was categorised as low, moderate or high. χ 2 Tests were used to look for associations between categorical variables and Chlamydia test positivity. A Poisson regression model was fitted to look at the effect of the number of people in the clinic on the number of positive results in a given day. As some clinics were only run on certain days of the week, a sensitivity analysis was later performed with attendances at non-daily clinics removed. Results: All dummy samples tested negative and we did not find evidence of an association between daily Chlamydia positivity and clinic attendance. Conclusions: It is unlikely that environmental or cross-contamination of CT has lead to significant numbers of false positive results. Laboratories check for possible cross-contamination routinely. The extension of this simple routine practice to all clinical areas could provide quality assurance, improving confidence in the results in clinics.